أفق الخطاب النقدي ومنطلقاته المعرفية والفكرية والفلسفية في مشروع إقبال الحضاري - عاشور مزيلخ (International Institute of Islamic Thought, 2016)
تدرس هذه الورقة المنطلقات المعرفية والفكرية والفلسفية لخطاب محمد إقبال في مشروعه الحضاري، المتميز بطابعه النقدي وبالتحليل المنطقي الرزين، وتبين إسهامه الإيجابي في نقد تلك المنطلقات الخاصة بالحضارة الغربية في مقابل ما يلزم لبناء الهوية المميزة لذات الإسلامية وخصوصيتها. وتعتمد الدارسة على كتاباته ومؤلفاته التي تمثل في مجموعها مشروعاً نقدياً لبناء الشخصية الإسلامية المعاصرة. وأظهرت هذه الدراسة تميز خطاب إقبال النقدي بطابع خاص هدفه ترقية المجتمع روحياً، والالتزام بالتربية الروحية كما أمر بها الإسلام، وتأسيس منظومة المعرفة الإسلامية قوامها القرآن، والحديث، والإجماع، والقياس. This paper examines the epistemological, intellectual and philosophical premises of critical discourse of Iqbal cultural project which is distinguished by its outstanding critical nature and sober logical analysis. The paper delineates the positive contribution of his criticism premises of Western civilization, and what it takes to construct a distinctive Islamic self- identity. This study shows that Iqbal critical discourse is characterized by for spiritual nature to uplif the Muslim Society, develop commitment to spiritual education as ordained by Islam, and build Islamic knowledge system based on Holy Quran, Prophetic Hadith, consensus- Ijma' and deductive analogy- qiyas.